Yesus Kristus Sebagai Batu Penjuru: Memaknai Keberadaan Kristus Ditengah Penderitaan Berdasarkan Kitab 1 Petrus 2:1-10 - Erika Yusthina Balol; Abad Jaya Zega (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This article discusses the role of Jesus Christ as the "Cornerstone" in the context of the Christian life and how its meaning becomes increasingly relevant when we face trials and challenges in life. Jesus Christ as the "Cornerstone" is a metaphor that comes from the Book of 1 Peter in the New Testament of the Christian Bible. This concept reflects the strength, stability, and protection given by Christ to His people. In this paper, we explore the significance of this concept and how it provides inspiration and hope to individuals facing trials and adversity. We also detail how faith in Jesus Christ as the “Cornerstone” can guide us through life's trials. In conclusion, this article explores how important it is to understand the presence of Christ in facing the trials that often come in our journey as believers.